Control of Concrete Segregation and Quality Enhancement Using Continuous Mixer Units - Tek Raj Gyawali; Prem Narayan Adhikari; Suman Dahal (Advances in Civil Engineering)
Managing concrete segregation during transportation and pouring at construction sites is posed as a substantial challenge. The utilization of continuous mixer units to address segregation and enhance the quality of concrete is discussed in this paper. These mixer units were tested in both horizontal (M–Y mixer) and vertical (ESG mixer) setups. “M–Y” signifies “Maeda–Yamada,” and “ESG” stands for “Energy Saving Gravity.” Fly ash paste and water, representing segregated paste, were used for remixing in the M–Y mixer, while segregated concrete was used in the ESG mixer units to evaluate whether both types of mixer units enhanced the quality of the segregated materials. In the M–Y mixer, the successful mixing of fly ash paste and water was achieved, leading to the attainment of the desired higher water-to-powder ratio. The paste content was increased from 40% to 50% and 60%. When the initially segregated concrete was introduced into the ESG mixer, it underwent a transformation into well-mixed concrete, exhibiting a slump value of 13.5 cm. The 28-day compressive strength of the segregated concrete witnessed a significant improvement, being elevated from 11.9 to 39.5 MPa. During transportation on the conveyor belt, the concrete was subject to segregation, resulting in a 9.4% reduction in compressive strength. Additionally, during descent through the chute, a decrease of 16.1% was observed. However, through careful adjustments of the ESG mixer units in the chute, the concrete’s performance was enhanced to a level comparable to that achieved at the batching plant. The application of continuous mixer units contributed to the improvement of both the workability and strength of the segregated concrete. This result signifies the improvement in the strength, serviceability, and durability of concrete structures with the enhancement of concrete quality at construction sites.